1986
DOI: 10.1227/00006123-198604000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Experience with External Pneumatic Calf Compression in Neurology and Neurosurgery

Abstract: This report reviews our experience with external pneumatic compression (EPC) therapy in preventing clinically evident deep venous thrombosis (DVT) and pulmonary emboli (PE) in neurological and neurosurgical patients. A total of 523 patients admitted to the Departments of Neurology and Neurosurgery at the Massachusetts General Hospital from December 1980 through January 1984 are included. The incidence of DVT despite EPC use was 2.3%. The incidence of PE diagnosed by lung scan and usually confirmed by angiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 0 publications
0
13
0
2
Order By: Relevance
“…Reducing the pressure support mode or decreasing the daytime rate of intermittent mandatory ventilation with increasing periods off the ventilator generally occurs at the discretion of the treating physician. 24 The incidence of complications related to prophylactic heparin is very low. Patients with electrophysiologic evidence of severe GBS may not be candidates for early weaning and prolonged weaning may be anticipated in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the pressure support mode or decreasing the daytime rate of intermittent mandatory ventilation with increasing periods off the ventilator generally occurs at the discretion of the treating physician. 24 The incidence of complications related to prophylactic heparin is very low. Patients with electrophysiologic evidence of severe GBS may not be candidates for early weaning and prolonged weaning may be anticipated in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study with non-randomized controls suggested that deep vein thrombosis can be successfully prevented by the use of pneumatic devices [78]. A Cochrane review on the use of graduated compression stockings or intermittent pneumatic compression in patients with stroke did not find support for the use of either method [79].…”
Section: Aneurysmal Sah – Ruptured Aneurysm (Ria)mentioning
confidence: 99%
“…The incidence of DVT and subsequent PE in neurosurgery patients has been reported to be as high as 25%, and the PE mortality rate has been reported to range from 9% to 50% (16, 17). The important risk factors in neurosurgical surgery are the type of surgery (cranial, spinal, or vascular), duration of surgery, cancer, infection, immobilization, venous stasis, chronic lower extremity swelling, lower extremity trauma, advanced age, CHF, obesity, and sleep apnea.…”
Section: Neurosurgerymentioning
confidence: 99%